IMPLEMENTATION ANALYSIS OF E-PROCUREMENT IN INCREASING SMALL AND MEDIUM ENTERPRISE PARTICIPATION IN MALANG REGENCY - Kadarisman, Mohammad Rasul (Awang Long Law Review, 2024)
E-procurement (electronic procurement of goods and services) is the digital transformation of government procurement processes based on the internet. It offers opportunities to make procurement more transparent, effective, efficient, and accountable. The implementation of E-procurement is one manifestation of good governance. However, various regulations that encourage the participation of SMEs (Small and Medium Enterprise) in government procurement have not been utilized properly. This research was conducted to analyze the implementation of E-procurement in increasing the SME’s participation in Malang Regency. This study adopted an explanatory research design using a quantitative approach with a sample size of 75. The analysis results state that there is a significant relationship between the performance of procurement services, leadership, e-procurement, and the enhancement of SMEs' participation in Malang Regency.